2010
DOI: 10.1039/c0dt00190b
|View full text |Cite
|
Sign up to set email alerts
|

Substituted [Cu(i)(POP)(bipyridyl)] and related complexes: Synthesis, structure, properties and applications to dye-sensitised solar cells

Abstract: The synthesis and subsequent spectroscopic, electrochemical, photophysical and computational characterisation of a series of heteroleptic Cu(I) complexes of general formula: [CuPOP{4,4'(R)-bipyridyl}][BF(4)] and [CuPOP{4,4',6,6'(R)-bipyridyl}][BF(4)] is described (POP = bis{2-(diphenylphosphanyl)phenyl} ether; R = Me, CO(2)H, CO(2)Et. The steric constraint imposed by the POP ligand can impede distortion towards square planar geometry upon MLCT excitation or oxidation and this is explored in the context of vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
65
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 41 publications
(31 reference statements)
12
65
0
Order By: Relevance
“…Both B3LYP/LANL2DZ and B3LYP/6-31g(d,p) have been shown predict calculated structures good agreement with those determined experimentally for large organometallic compounds. 37 However, the improper inclusion of dispersion interactions within B3LYP is of concern in the study of non-covalently bound complexes, such as those in this work. As a comparison the M05-2X functional of Zhao and Truhlar, 38 which has been shown to recover significantly more mid-range correlation than B3LYP, 39 at a similar computational cost was also tested, again, in combination with the LANL2DZ basis set.…”
Section: Methodsmentioning
confidence: 99%
“…Both B3LYP/LANL2DZ and B3LYP/6-31g(d,p) have been shown predict calculated structures good agreement with those determined experimentally for large organometallic compounds. 37 However, the improper inclusion of dispersion interactions within B3LYP is of concern in the study of non-covalently bound complexes, such as those in this work. As a comparison the M05-2X functional of Zhao and Truhlar, 38 which has been shown to recover significantly more mid-range correlation than B3LYP, 39 at a similar computational cost was also tested, again, in combination with the LANL2DZ basis set.…”
Section: Methodsmentioning
confidence: 99%
“…Reaction of Cu(N≡CCH 3 ) 4 ClO 4 with BrphenBr or BrbpyBr and diphosphine ligand BINAP or xantphos in a 1:1:1 stoichiometric ratio under oxygen-free conditions following by crystallization from dichloromethane/hexane afforded four mononuclear complexes, [Cu(BrphenBr)(BINAP)]ClO 4 (1), [Cu(BrbpyBr)(BINAP)]ClO 4 (2), [Cu(BrphenBr)(xantphos)]ClO 4 (3) and [Cu(BrbpyBr)(xantphos)]ClO 4 (4) in good yields. All the complexes 1−4 are stable to air and moisture in the solid state.…”
Section: Synthesesmentioning
confidence: 99%
“…Introduction of bromine atoms into diimine ligands with bromine far from coordination sphere is expected to both extend the conjugacy of diimine ligands and enhance the phosphorescence emission due to the heavy atom effect of bromine atom. Here, we will report the syntheses, structures and solid luminescence behavior of four mononuclear Cu(I)-diimine-diphosphine complexes constructing from α-diimines 3,8-dibromo-1,10-phenanthroline (BrphenBr) or 5,5′-dibromo-2,2′-bipyridine (BrbpyBr), the bulky diphosphine ligands (±)-2,2'-bis(diphenylphosphino)-1,1'-binaphthalene (BINAP) or rigid 9,9-dimethyl-4,5-bis(diphenylphosphino)-9H-xanthene (xantphos) and [Cu(N≡CCH 3 ) 4 ]ClO 4 . The structures of these ligands are depicted in Chart 1.…”
mentioning
confidence: 99%
“…Among them, polypridyl Cu(I) complexes are attracting attention since Sauvage and coworkers [7] firstly used them in DSSCs as alternatives to polypridyl Ru(II) sensitizers. Further investigations by Constable [8e11] and Robertson [12] confirmed that Cu(I)-based complexes could be potentially efficient sensitizers coupled with mesoporous TiO 2 electrode in DSSCs [13]. Cu(I)-coordinated complexes, as sensitizers, exhibit prominent photophysical and photochemical properties [14e16], including the long-lived metal-to-ligand charge transfer (MLCT) excited states due to the d 10 configuration [17], broad MLCT transition bands in the visible region [13e18], and the potent reductant for the thermally equilibrated MLCT state [19].…”
Section: Introductionmentioning
confidence: 99%